Nitrogen-doped carbon dots with excitation-independent long-wavelength emission produced by a room-temperature reaction. Issue 80 (15th September 2016) - Yang, Chenhui; Zhu, Shoujun; Li, Zhenglin; Li, Zhuo; Chen, Chong; Sun, Lei; Tang, Wei; Liu, Rui; Sun, Ye; Yu, Miao
Abstract : Nitrogen-doped carbon dots (CDs) have been produced by a new facile "bottom-up" synthesis, using the room-temperature reaction between acetonitrile and sodium-naphthalene. Abstract : Nitrogen-doped carbon dots (CDs) have been produced by a new facile "bottom-up" synthesis, using the room-temperature reaction between acetonitrile and sodium-naphthalene. The obtained hydrophobic CDs are monodisperse (∼2.6 nm) and present an excitation-independent emission at ∼588 nm with a small full width at half-maximum (FWHM) of ∼52 nm. The CDs can be simply modified to be hydrosoluble and have been demonstrated to be an efficient red-emission agent for both in vivo and in vitro bioimaging.